The Association between Antenatal Tea Drinking and Hypertensive Disorders of Pregnancy: A Systematic Review and Meta-Analysis - Ahmed Arafa; Haytham A. Sheerah; Omar Khaled Alzaydan; Yasser Sabr (MDPI AG, 2024)
Several adverse maternal outcomes have been linked to the excessive consumption of caffeine during pregnancy. Tea is an important source of caffeine. Hypertensive disorders of pregnancy (HDP) are common pregnancy complications with unfavorable maternal and fetal complications. This study aimed to investigate the relationship between antenatal tea drinking and HDP using a meta-analysis of available evidence. We systematically retrieved eligible studies before computing the pooled odds ratio (OR) and 95% confidence interval (CI) of HDP for women who reported the highest versus the lowest frequencies of antenatal tea drinking. We used the I2 statistic to measure heterogeneity across studies and the test for funnel plot asymmetry to evaluate publication bias. The results showed that the highest frequencies of antenatal tea drinking were associated with increased odds of HDP (pooled OR = 1.16, 95% CI: 1.01, 1.33). We identified no signs of heterogeneity across studies (I2 = 0.0% and p-heterogeneity = 0.498) or publication bias (z = 0.791 and p-publication bias = 0.429). When the outcome was limited to (pre-)eclampsia, the association became statistically non-significant (pooled OR = 1.28, 95% CI: 0.86, 1.89, I2 = 0.0%, and p-heterogeneity = 0.751). In conclusion, our results indicated that the highest frequency of antenatal tea drinking was positively associated with HDP. Pregnant women should be advised against excessive tea consumption. Still, future prospective cohort studies, considering the effects of different tea types and caffeine content, are needed to confirm our conclusions.